Quran sensoryREADY - Mai Salameh; Fatina Al Taher (My University, 2025)
Technology has been infused into education in the past years, which has completely changed the ways children learn, interact, and engage with information. Nevertheless, a lot of modern tools, such as computers and tablets designed for older children, do not take into account younger children ages 3 to 12 and their unique sensory, cognitive, and developmental needs. This gap in educational technology is especially pertinent within special education and religious learning, early childhood development, and early childhood care. In response to these hurdles, SensoryREADY has been developed as a communication platform that is customizable, interactive, and sensory-friendly, providing help in various learning environments. With its use by teachers, therapists, and parents, the platform enhances learning and communication for children who require strong, structured, visual, and auditory stimuli. One of the key innovations of SensoryREADY is its Controller-Receiver-User model, which guarantees a combination of high flexibility alongside low intuitive interaction. Adaptive learning interventions can be gained from this model, which are crafted to the needs of every single child. The app’s modern educational techniques make it stand out and provide purpose alongside the more advanced applications. Alongside the more advanced applications for the Quran, the app serves as a purpose-built aid for kids and adults, memorizing and reciting the Quran.